An Official Outbreak Investigation of Acute Haemorrhagic Diarrhoea in Dogs in Norway Points to Providencia alcalifaciens as a Likely Cause - Hannah Joan Jørgensen (MDPI AG, 2021)
An outbreak investigation was initiated in September 2019, following a notification to the Norwegian Food Safety Authority (NFSA) of an unusually high number of dogs with acute haemorrhagic diarrhoea (AHD) in Oslo. Diagnostic testing by reporting veterinarians had not detected a cause. The official investigation sought to identify a possible common cause, the extent of the outbreak and prevent spread. Epidemiological data were collected through a survey to veterinarians and interviews with dog owners. Diagnostic investigations included necropsies and microbiological, parasitological and toxicological analysis of faecal samples and food. In total, 511 dogs with acute haemorrhagic diarrhoea were registered between 1 August and 1 October. Results indicated a common point source for affected dogs, but were inconclusive with regard to common exposures. A notable finding was that 134 of 325 faecal samples (41%) cultured positive for Providencia alcalifaciens. Whole genome sequencing (WGS) of 75 P. alcalifaciens isolates from 73 dogs revealed that strains from 51 dogs belonged to the same WGS clone. Findings point to P. alcalifaciens as implicated in the outbreak, but investigations are needed to reveal the pathogenic potential of P. alcalifaciens in dogs and its epidemiology.